2020
DOI: 10.14295/transportes.v28i3.1797
|View full text |Cite
|
Sign up to set email alerts
|

Public transport usage among university students: what to expect based on customer satisfaction survey (CSS) analysis

Abstract: Pesquisas de Satisfação do Consumidor são ferramentas valiosas tanto para gestores públicos quanto para empresas de operação. Estas fornecem informações úteis para a compreensão das necessidades dos usuários de transporte público, para a definição de objetivos mais efetivos e para fazer investimentos mais assertivos. Na literatura, a combinação de segmentação de mercado e a comparação entre satisfação e importância relativa foi poucas vezes estudada. Este estudo investiga a tendência de adoção contínua do tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 45 publications
(62 reference statements)
1
1
0
Order By: Relevance
“…A Slovenian study showed that PPT tariffs had a significant impact on travel behavior [72]. The findings are consistent with those of previous studies indicating that the strategy most likely to encourage students to switch from cars to PPT is to make PPT cheaper via subsidized fares [2,10,49,73]. Previous studies [29,74,75] have also indicated that the establishment of a high-frequency national bus/coach service and investment in a motorway network to enhance the speed of bus/coach travel are effective measures to promote the use of PPT.…”
Section: Discussionsupporting
confidence: 83%
“…A Slovenian study showed that PPT tariffs had a significant impact on travel behavior [72]. The findings are consistent with those of previous studies indicating that the strategy most likely to encourage students to switch from cars to PPT is to make PPT cheaper via subsidized fares [2,10,49,73]. Previous studies [29,74,75] have also indicated that the establishment of a high-frequency national bus/coach service and investment in a motorway network to enhance the speed of bus/coach travel are effective measures to promote the use of PPT.…”
Section: Discussionsupporting
confidence: 83%
“…Specifically, the Customer Satisfaction Indexes (CSIs) were chosen to be collected and analyzed as they measure the quality of the provided services based on the users' judgment with the help of a numerical scale (Likert scale in this case) [19,20]. As the descriptive statistics analysis provides an insight to the collected data [21,22], the in-depth analysis examines the correlation of predefined factors, specifically those used by the algorithm for the calculation of the level of satisfaction for the above-mentioned transport modes, with the majority of these predefined factors having been used in other case studies as well [23][24][25].…”
Section: Literature Reviewmentioning
confidence: 99%